Synthesis of large (2+3) salicylimine cages with embedded metal-salphen units - Uhrmacher, Fabian; Elbert, Sven; Rominger, Frank; Mastalerz, Michael (European journal of inorganic chemistry, 2022)
Metal salphen containing complexes have found a broad variety of applications in catalysis as well as material science. Most of these materials are either mono-nuclear complexes or polymeric network materials. Discrete macromolecular polynuclear salphens are still rare and mostly two-dimensional structures. Here we present three-dimensional trinuclear Ni(II)- and Pt(II)-cage compounds with a covalently bound [2+3] salicylimine cage backbone. The solubility of the cages allowed their investigation by spectroscopic methods. Furthermore, the Pt(II) derivative was investigated by single crystal X-ray structure analysis revealing that the presented cage compounds possess the largest intrinsic void of metal salphen cages reported till date.
Online veröffentlicht: 28. Oktober 2021
Im Titel steht der Ausdruck "2+3" in eckiger Klammer
Gesehen am 09.02.2022